ANALISIS YURIDIS PUTUSAN MAHKAMAH AGUNG NOMOR 113 PK/TUN/2020 TENTANG PENERBITAN SERTIFIKAT PENGGANTI ATAS TANAH YANG SUDAH DIPERJUALBELIKAN - Karima, Tirsa Okta; Wardhana, Mahendra (NOVUM : JURNAL HUKUM, 2019)
The dispute was occurred between Ho Kiarto and the Head of the Surabaya City Land Office I in the Supreme Court Decision Number 113 PK/TUN/2020 is evidence of a dispute over the issuance of a replacement certificate for land that has been traded. This dispute began with H Moch Goefron Masyhuri who had sold the land of the two objects of dispute to Ho Kiarto so that he was the physical and/or de facto holder of the existence of SHM No. 264/Kel. Tambaklangon and SHM No. 444/Kel. Tambaklangon on behalf of H. Moch Goefron Masyhuri, but Badrus Sholeh (Defendant II Intervention) as the heir of H. Moch Goefron Masyhuri has reported to the Head of Surabaya City Land Office I for the loss of the two objects of dispute, and on this report the Head of Surabaya City Land Office I issued SHM Number 445/Kel. Tambak Sarioso on Replacement of SHM Number 264/Kel. Tambaklangon and SHM Number 690 / Kel. Tambak Sarioso for the replacement of SHM Number 444/Kel. Tambaklangon on behalf of H. Moch Goefron Masyhuri so that in this case the issuance of a replacement certificate by the Head of the Surabaya City Land Office I has contravened to the Legislations (Peraturan Perundang-undangan) chapter 56 paragraph (1) of Government Regulation No. 24/1997 and does not apply the principles of the General Principles of Good Government (Asas-Asas Umum Pemerintahan Yang Baik/AAUPB), especially the Principle of Accuracy in its issuance.